RFID Hostel Management System - MA'RADZI, AHMAD ALABQARI; Zakaria, Muhammad Ailman Arif; Ishak, Muhammad Aiman; Muhamad Azman, Athirah (Multidisciplinary Applied Research and Innovation, 2020)
The RFID project is a system that allow warden to control the hostel or reduce the usage of electricity at the hostel. This systems use Arduino UNO as the microcontroller to control all of the component that we used. It is using software Arduino IDE as a platform to make the coding and also use RF transceiver. This project can make the warden to switch off the lamp easily without having to go every room that can save time and warden’s energy. The project can also educated the resident of hostel especially student to follow the hostel laws such as room's light must be switch off after 11.00 pm. Now warden can easily control the rate of electricity usage in the hostel by using this project.